2017
DOI: 10.1007/s10103-017-2299-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of photobiomodulation therapy and topical non-steroidal anti-inflammatory drug on skeletal muscle injury induced by contusion in rats—part 2: biochemical aspects

Abstract: Muscle injuries trigger an inflammatory process, releasing important biochemical markers for tissue regeneration. The use of non-steroidal anti-inflammatory drugs (NSAIDs) is the treatment of choice to promote pain relief due to muscle injury. NSAIDs exhibit several adverse effects and their efficacy is questionable. Photobiomodulation therapy (PBMT) has been demonstrated to effectively modulate inflammation induced from musculoskeletal disorders and may be used as an alternative to NSAIDs. Here, we assessed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 45 publications
0
17
1
Order By: Relevance
“…Therefore, finding alternatives to these therapies for high-risk patients seems to be the logical option. Some possibilities may be topical NSAIDs, which have fewer side effects [119] or other modalities such as photobiomodulation (low level laser therapy; LLLT) [120]. Animal studies suggest that at the right dose, laser therapy can be more effective at modulating the inflammatory process, than topical NSAIDs which treat pain alone [120].…”
Section: Management Of Musculoskeletal Diseasesmentioning
confidence: 99%
“…Therefore, finding alternatives to these therapies for high-risk patients seems to be the logical option. Some possibilities may be topical NSAIDs, which have fewer side effects [119] or other modalities such as photobiomodulation (low level laser therapy; LLLT) [120]. Animal studies suggest that at the right dose, laser therapy can be more effective at modulating the inflammatory process, than topical NSAIDs which treat pain alone [120].…”
Section: Management Of Musculoskeletal Diseasesmentioning
confidence: 99%
“…According to de Paiva Carvalho [10], who also observed similar results in muscle lesions, but in nondiabetic rats, the most interesting result in an antiinflammatory therapy is the decrease in COX-2. Tomazoni et al [15], using the same injury protocol and the same parameters of PBMT, demonstrated a decrease in the gene expression of COX-2 in non-diabetic animals. Our findings are in agreement with several studies that demonstrate a decrease in inflammatory markers in different experimental models of diseases [15,[21][22][23][24].…”
Section: Discussionmentioning
confidence: 93%
“…Tomazoni et al [15], using the same injury protocol and the same parameters of PBMT, demonstrated a decrease in the gene expression of COX-2 in non-diabetic animals. Our findings are in agreement with several studies that demonstrate a decrease in inflammatory markers in different experimental models of diseases [15,[21][22][23][24]. Ramos et al [25] found that PBMT (3 J) decreased gene expression of inflammatory markers after stretch muscle injury.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations